Desain Bahan Ajar Tambahan Untuk Meningkatkan Minat Siswa Dalam Belajar Bahasa Ingggris - Maliqul Hafis; Sahrawi Sahrawi (Educatio, 2019)
AbstractThis research and development aims to describe the design and feasibility of the quality of English teaching materials for junior high school students. The research uses five out of ten stages based on Gall Borg (2007) determination of the stages of research including: (1) research and information collecting, (2) planning, (3) developing preliminary forms of product, (4) preliminary field testing, (5) main product revision. The researchers get an evaluation of learning material from several evaluators. The results obtained show that almost all opinions are in agreement and agree. 33.33% of evaluators agree that infographic can generally help students understand the lesson. The remaining 66.66% of students strongly agree. The evaluator agreed that graphs and drawings were broadly related to teaching material. All evaluators also agreed that the material was interestingly designed. This shows that all evaluators agreed in accordance with the statement instrument. Thus, the product results can be used by teachers in helping students in the learning process.